Research and innovation priorities for enabling legume scaling for development outcomes in Tanzania - Varley, Ciara; Johnston, Angharad; Recha, John W.M.; Ndlovu, Noel; Longwe, Kareem; Munthali, Timalizge W; Silumesi, Mwala; Mushangure, Remeredzai O; Kalumo, Decolius; Kaonga, Tione P; Kinkese, Theresa; Breen, Caitilin; et al. (University of Galway and IITA, 2024)
Legumes are critical to agriculture, food security and economic development in Tanzania. The EU-funded LEG4DEV project is conducting research & innovation activities with scaling partners in Tanzania to enable them to more eiectively scale legumes for development outcomes (productivity, health & nutrition, sustainability, livelihood security). Following an intensive schedule of bilateral meetings with stakeholders and potential scaling partners in Tanzania, the LEG4DEV project organised and ran a “Legumes for Development” multistakeholder research prioritisation workshop on 31st of March 2023 in Dar es Salaam, Tanzania (Annex 1). The LEG4DEV Multistakeholder workshop was held at the White Sands Hotel and was opened by John Sariah from the Tanzania Agricultural Research Institute (TARI). He highlighted the importance of legume scaling to national development goals of Tanzania in relation to agricultural productivity, health & nutrition, sustainability and livelihoods. The LEG4DEV Multistakeholder Workshop (Tanzania) was attended by 51 attendees from government, research organisations, universities, donors, NGOs, farmers organisations and companies (Annex 2). The workshop was organised around the six work packages of the LEG4DEV project where workshop participants worked in interdisciplinary teams to identify their highest priority research questions (both technical and policy/institutional) that the LEG4DEV project research could focus on in Tanzania to better enable legume scaling at the national level.